Market Orientation in the Sudanese Manufacturing Firms (An Empirical Study) - Abdelwahab, Manal Elzien; Khalifa, Ahmed Hamza (Gezira Journal of Economic and Social Sciences; مجلد 1 عدد 2 (2010), 2010)
The researcher used the stratified random sampling method. A total number of 91 companies out of 114companies participated (with a response rate of 80%).To analyze the data, the researcher used descriptive statistics including methods like tables, frequencies, and averages to assess the were tested using sophisticated methods like multiple regression analysis (stepwise regression analysis) and multivariate analysis of variance (MANOVA). The findings of this study confirm the applicability of the empirical model in Sudan. Ten antecedents/factors determine the market orientation of the manufacturing companies in Sudan that including, top management emphasis, management training, risk aversion, formalization, market based reward system, interdepartmental conflict, interdepartmental connectedness, competition, market turbulence, and general economy. Only three antecedents, formal marketing education, centralization and technological turbulence are not effective in determining the MO and its components in Sudan.  The findings also confirm that the MO significantly contributes to the achievement of superior performance, both the economic and non-economic. The most important recommendations of this research indicate that the model of MO developed for Sudan makes a significant contribution to the MO literature in that country particularly, to the manufacturing companies. The Sudanese organizations can use this model as a guide for their businesses. This model confirms that both superior economic and non-economic performance of business are determined by the level of MO of an organization. The empirical findings of this investigation have policy implications for large companies in developing countries in general and Sudan in particular. It is expected that this model will be used as a starting point for further researches and to be tested in other countries in the world, both developed and developing.